Tangential Bicortical Locked Fixation Improves Stability in Vancouver B1 Periprosthetic Femur Fractures: A Biomechanical Study - Lewis, Gregory S. (J Orthop Trauma, 2015)
OBJECTIVES: The biomechanical difficulty in fixation of a Vancouver B1 periprosthetic fracture is purchase of the proximal femoral segment in the presence of the hip stem. Several newer technologies provide the ability to place bicortical locking screws tangential to the hip stem with much longer lengths of screw purchase compared to unicortical screws. This biomechanical study compares the stability of two of these newer constructs to previous methods. METHODS: Thirty composite synthetic femurs were prepared with cemented hip stems. The distal femur segment was osteotomized, and plates were fixed proximally with either: (1) cerclage cables; (2) locked unicortical screws; (3) a composite of locked screws and cables; or tangentially directed bicortical locking screws using either (4) a stainless steel LCP system with a Locking Attachment Plate (Synthes), or (5) a titanium alloy NCB system (Zimmer). Specimens were tested to failure in either axial or torsional quasi-static loading modes (n = 3) after 20 moderate load pre-conditioning cycles. Stiffness, maximum force, and failure mechanism were determined. RESULTS: Bicortical constructs resisted higher (by an average of at least 27%) maximum forces than the other three constructs in torsional loading (p<0.05). Cables constructs exhibited lower maximum force than all other constructs, in both axial and torsional loading. The bicortical titanium construct was stiffer than the bicortical stainless steel construct in axial loading. CONCLUSIONS: Proximal fixation stability is likely improved with the use of bicortical locking screws as compared to traditional unicortical screws and cable techniques. In this study with a limited sample size, we found the addition of cerclage cables to unicortical screws may not offer much improvement in biomechanical stability of unstable B1 fractures.